National medical service
1943-10-20 1943 1940s 15 pages -7- Interdepartmental Committee on Rehabilitation that there should not only be reorganisation of Fracture Hospital Work and segregation of fracture cases in special wards under continual surgical team work, but also rehabilitation centres for the terminal stages of reconditioning until the full restoration of capacity for work or the patient left with a residual disability for retraining for other work, the voluntary hospitals admitted that in their crippled financial state the additional expenditure could not be undertaken. It has to be realised that there are only just over 1,000 voluntary hospitals in Great Britain, varying in type from the smallest cottage hospitals (where the medical staff consists of rural general practitioners) to the well-known larger voluntary hospitals with attached Meeical [Medical] Teaching Schools. When discussion takes place on voluntary hospitals, the great tendency, because of the well directed cumulative effect of propaganda and showmanship, is for the ordinary mind to think of the larger voluntary hospitals with "unpaid consulting staffs. There are only about 24 Medical Teaching Schools in the country and these with the voluntary hospitals in the larger cities received the greatest prominence, and the most favourable press puffs. The cost of running the voluntary hospitals on present lines is only about £18 million a year - a comparatively small amount for the institutional treatment of cases the majority of which are either acute or subacute cases (emergencies) or for investigation. Under a National Health Service, with well-equipped up-to-date hospitals, the cost would probably be increased by 60 per cent. or more. It is known for example that on many occasions the consultant surgeons in voluntary hospitals have to bring their own surgical instruments for many and not even special operations. Accommodation for nurses and resident medical officers in voluntary institutions needs much improvement. The residents are frequently poorly paid and so have to increase their remuneration by charging fees for preliminary reports on cases in hospital, as for example in workmen's compensation cases, so that a worker may make four payment contributions for hospital services. The consulting staff of Physicians and Surgeons in voluntary hospitals are not paid monetarily. But because of the Status, the Clientele of medical students, and the growing experience from contact with most interesting cases, and discussion with these consulting staff friends, the advantages are great, and later by the medical students when future practising doctors sending them private cases for an opinion, diagnosis or treatment, actual financial benefit is derived from an extensive cumulative consulting practice. And the voluntary hospital consultant is free to act on his own responsibility in attention or treatment to patients and for trial of any treatment method without fear of any investigation. Medical Teaching Schools attached to voluntary hospitals receive the benefit of a National Education grant through the University Grants Committee (a special body for recommending University grants) provided the medical students are being prepared for a University medical Degree. As a consequence an interprofessional and inter-institutional contention has developed here. Many poorer students cannot afford the longer period and stiffer examinations of the University degrees as against the lower qualifying examinations and diplomas. As the teaching school benefits from the University grants, the tendency especially more recently is to decline to accept students avowedly aiming at the qualifying diplomas of the Royal Colleges. The Colleges and their tutorial staffs are now objecting to this development. Many 292/847/2/113